Assessment of Rainwater Quality from Rainwater Storage in Ende, East Nusa Tenggara Province, Indonesia - Yohanes Erik Kurniawan Nggae; Intan Supraba; Radianta Triatmadja (Universitas Pelita Harapan, 2026)
Using rainwater as an alternative water source requires careful attention to its quality, particularly in simple storage systems. This study aims to analyze changes in the physical, chemical, and microbiological quality of rainwater stored in a tank over a specified period, as well as the effects of maintenance practices on rainwater harvesting systems. The research methodology involved collecting samples of untreated rainwater and rainwater stored in a tank over four weeks. Physical parameters analyzed included color, turbidity, and total dissolved solids (TDS); chemical parameters included pH; and microbiological parameters included total coliforms and Escherichia coli. The results indicate that poor roof surface and gutter system cleanliness led to increased turbidity and noticeable changes in rainwater color. Following roof and gutter cleaning, improvements in the physical quality of the stored rainwater were observed. However, an anomaly in turbidity occurred during the third week, reaching 52 NTU. TDS values decreased throughout the storage period, while the pH of the rainwater remained within a neutral range. From a microbiological perspective, the concentrations of total coliforms and E. coli decreased significantly over the storage period, presumably due to limited nutrient availability and unfavourable environmental conditions for bacterial growth. The boiling process was effective in reducing bacterial concentrations; however, total coliforms and E. coli were still detected at levels of 11 CFU/100 mL and 4.4 CFU/100 mL, respectively. These findings demonstrate that stored rainwater requires further treatment prior to use, particularly for potable purposes.